Risk Management Practice and Sustainability of Community Policing Projects: A Case of Nyumba-Kumi Community-Policing Project in Kasarani Constituency in Nairobi County, Kenya - Lerina, Josephine Naanyu; Chandi, John Rugendo; Njue, Nicasio Gicovi (European Journal of Applied Sciences, 2023)
Sustainability of projects is very important in promoting long-term gains to the beneficiaries. However, risks are ranked among the most constraining factors in attaining long-term impacts of projects focused on promoting peace and security in the community. The study investigated the influence of risk management practice on sustainability of Nyumba-Kumi community-policing project in Kasarani Constituency in Nairobi County, Kenya. The objectives were to establish the influence of participatory risk assessment, risk planning, risk communication and risk monitoring on sustainability of community-policing project. Risk theory and sustainability theory anchored the study. Descriptive survey was adopted. The targeted population was 222 project coordinators. A sample size of 144 was obtained using Krejcie & Morgan formula and stratified random sampling. Structured questionnaires and interview guide were used to collect data. Split-half method was used in testing reliability at Cronbach`s alpha ≥0.7. Quantitative data was analyzed using frequencies, mean, percentages, standard deviation, Pearson-Correlation method and regression analysis. The research model was tested using F-test at 95% confidence interval. Qualitative data was analyzed through content analysis. The results from inferential statistics showed that risk management practice has statistically significant effect on sustainability of Nyumba-Kumi community-policing project. The strength of influence decreased in the following order: risk monitoring (r=0.72), risk planning (r=0.60), participatory risk assessment (r=0.47) and risk communication (r=0.39). The accounted for 59% variation in the sustainability of Nyumba-Kumi community-policing project (for R2= 0.59). Thus, risk management practice was concluded to be an important factor for promoting sustainability of community-policing project